The Bondwoman's Narrative - Crafts, Hannah (Time Warner Books, 2002)
An unprecedented historical and literary event, this tale written in the 1850s is the only known novel by a female African American slave, and quite possibly the first novel written by a black woman anywhere. A work recently uncovered by renowned scholar Professor Henry Louis Gates, Jr., it is a stirring, page-turning story of "passing" and the adventures of a young slave as she makes her way to freedom...
Keywords: Fiction; Historical